Desa wisata Watu Ledhek Dusun Dayakan Kelurahan Sardonoharjo Kabupaten Sleman Daerah Istimewa Yogyakarta - Harsanto, Kevin Christian; Nusanto, Tri Suyud; Prasetyo, Danang (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2024)
The Real Work Lecture (Kuliah Kerja Nyata or KKN) conducted by students of STIPRAM Yogyakarta took place in Patihan, Bantul. The individual project I undertook was creating a promotional video for camping at Goa Cemara Beach. The driving factors included raising awareness, building trust, and attracting tourist interest. The inhibiting factors encompassed limited facilities, unpredictable weather, and technical knowledge gaps. The outcome was a 3-minute promotional video shared on social media platforms, yielding positive responses and boosting visits and revenue at Goa Cemara Beach. In conclusion, social media proves effective in promoting tourism, yielding favorable impacts for the local community.